The role of genetics and antibodies in sepsis - Giamarellos-Bourboulis, Evangelos J.; Opal, Steven M. (Annals of Translational Medicine; Vol 4, No 17 (September 13, 2016): Annals of Translational Medicine (Focused Issue on “Management of Infections in Septic Shock”), 2016)
During the course of sepsis when immunosuppression predominates, the concentrations of circulating immunoglobulins (IGs) are decreased and this is associated with adverse outcomes. The production of IGs as response to invasive bacterial pathogens takes place through a complex pathway starting from the recognition of the antigen (Ag) by innate immune cells that process and present Ags to T cells. The orchestration of T-helper (Th) lymphocyte responses directs specific B cells and ends with the production of IGs by plasma cells. All molecules implicated in this process are encoded by genes bearing single nucleotide polymorphisms (SNPs). Meta-analysis of case-control studies have shown that the carriage of minor frequency SNPs of CD14, TLR2 and TNF is associated with increased sepsis risk. The ambiguity of results of clinical trials studying the clinical efficacy of exogenous IG administration in sepsis suggests that efficacy of treatment should be considered after adjustment for SNPs of all implicated genes in the pathway of IG production.